2017
DOI: 10.1097/dad.0000000000000697
|View full text |Cite
|
Sign up to set email alerts
|

Primary Cutaneous Follicular Helper T-cell Lymphoma in a Patient With Neurofibromatosis Type 1: Case Report and Review of the Literature

Abstract: Patients with neurofibromatosis type 1 (NF-1) have a well-known predisposition for certain types of malignancies, including lymphoproliferative disorders. Cutaneous T-cell lymphoma (CTCL) has been reported in patients with NF-1, although it is considered a rare entity in this subset of patients. Cutaneous follicular helper T-cell lymphoma (CTFHCL) is a recently emerged rare subtype of CTCL with peculiar clinical and histopathological features and represents a diagnostic and therapeutic challenge. Only a few ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…16 In the literature, CD7 expression is variable in ENKTL and PC-TFHL. 3,4,8,10,16 In our case no. 1, CD7 expression was downregulated while CD7 was positive in case no.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…16 In the literature, CD7 expression is variable in ENKTL and PC-TFHL. 3,4,8,10,16 In our case no. 1, CD7 expression was downregulated while CD7 was positive in case no.…”
Section: Discussionmentioning
confidence: 46%
“…PC-TFHL is rare with only sporadic case reports. 3–10 Most cases present as multiple skin lesions. Le Tourneau et al 10 reported 2 such cases presenting as multiple primary skin lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no distinct relationship has been established, there have been multiple case reports of CTCL in patients with NF1 [87][88][89]. In these three case reports, two patients were diagnosed with mycosis fungoides [88,89] and one with a rare subtype of cutaneous follicular helper T-cell lymphoma [87]. While patients with NF1 are at higher risk of malignancies, there is no known predilection for CTCL specifically.…”
Section: Cutaneous T Cell Lymphomamentioning
confidence: 99%